Primary vaccination in adult patients after allogeneic hematopoietic stem cell transplantation – A single center retrospective efficacy analysis. Issue 33 (30th July 2021) - Sattler, Clara; Hoffmann, Petra; Herzberg, Philipp Yorck; Weber, Daniela; Holler, Barbara; Fehn, Ute; Plentz, Annelie; Beckhove, Philipp; Winkler, Julia; Edinger, Matthias; Herr, Wolfgang; Holler, Ernst; et al.
Highlights: Current revaccination strategy is efficient in the majority of alloHSCT patients. Low B cells and low IgGs are risk factors for failure of vaccination response. Chronic GVHD does not prevent successful revaccination. Chronic GVHD increases the risk for low response. Booster vaccines are associated with high risk of failure to respond to vaccination. Abstract: Allogeneic hematopoietic stem cell transplantation (alloHSCT) results in a loss of humoral immunity and subsequent risk for severe infections. Thus, re-vaccination is required but may fail due to incomplete immune reconstitution. We retrospectively analyzed predictors of immune response to primary vaccination applied according to the EBMT (European Blood and Marrow Transplantation Group) recommendations. Serologic response to vaccination against diphtheria (D), tetanus (T), Bordetella pertussis (aP) and Haemophilus influenzae (Hib) (administrated as combined DTaP-Hib-IPV vaccination) was studied in 84 alloHSCT patients transplanted between 2008 and 2015 (age at alloHSCT: 18.6–70.6 years). All patients with a relapse-free survival of ≥9 months, at least 3 consecutive vaccinations and absence of intravenous immunoglobulin administration within 3 months before and after vaccination met the primary inclusion criteria. Additionally, immunological response to a pneumococcal conjugate vaccine was analyzed in a subgroup of 67 patients. Patients' characteristics at the time of first vaccination were recorded. Responses were measured as vaccine-specific antibody titers. Regarding DTaP-Hib-IPV vaccination, 89.3% (n = 75) of all patients achieved protective titers to at least 3 of the 4 vaccine components and were thus considered responders. 10.7% (n = 9) of the patients were classified as non-responders with positive immune response to less than 3 components. Highest response was observed for Hib (97.4%), tetanus (95.2%) and pneumococcal vaccination (83.6%) while only 68.3% responded to vaccination against Bordetella pertussis. Significant risk factors for failure of vaccination response included low B cell counts (p < 0.001; cut-off: 0.05 B cells/nl) and low IgG levels (p = 0.026; mean IgG of responders 816 mg/dl vs. 475 mg/dl of non-responders). Further, a trend was observed that prior cGvHD impairs vaccination response as 88.9% of the non-responders but only 54.7% of the responders had prior cGvHD (p = 0.073). The results demonstrate, that the currently proposed vaccination strategy leads to seroprotection in the majority of alloHSCT patients.